AMPK activation protects against prostate cancer by inducing a catabolic cellular state - Lucy Penfold; Angela Woods; Alice E. Pollard; Julia Arizanova; Eneko Pascual-Navarro; Phillip J. Muckett; Marian H. Dore; Alex Montoya; Chad Whilding; Louise Fets; Joao Mokochinski; Theodora A. Constantin; et al. (Cell Reports, 2023)
Summary: Emerging evidence indicates that metabolic dysregulation drives prostate cancer (PCa) progression and metastasis. AMP-activated protein kinase (AMPK) is a master regulator of metabolism, although its role in PCa remains unclear. Here, we show that genetic and pharmacological activation of AMPK provides a protective effect on PCa progression in vivo. We show that AMPK activation induces PGC1α expression, leading to catabolic metabolic reprogramming of PCa cells. This catabolic state is characterized by increased mitochondrial gene expression, increased fatty acid oxidation, decreased lipogenic potential, decreased cell proliferation, and decreased cell invasiveness. Together, these changes inhibit PCa disease progression. Additionally, we identify a gene network involved in cell cycle regulation that is inhibited by AMPK activation. Strikingly, we show a correlation between this gene network and PGC1α gene expression in human PCa. Taken together, our findings support the use of AMPK activators for clinical treatment of PCa to improve patient outcome.